f(g(f(a), h(a, f(a)))) -> f(h(g(f(a), a), g(f(a), f(a))))

R

↳Removing Redundant Rules

Removing the following rules from

f(g(f(a), h(a, f(a)))) -> f(h(g(f(a), a), g(f(a), f(a))))

where the Polynomial interpretation:

was used.

_{ }^{ }POL(g(x)_{1}, x_{2})= x _{1}+ 2·x_{2}_{ }^{ }_{ }^{ }POL(h(x)_{1}, x_{2})= 1 + x _{1}+ x_{2}_{ }^{ }_{ }^{ }POL(a)= 0 _{ }^{ }_{ }^{ }POL(f(x)_{1})= x _{1}_{ }^{ }

All Rules of

R

↳RRRPolo

→TRS2

↳Overlay and local confluence Check

The TRS is overlay and locally confluent (all critical pairs are trivially joinable).Hence, we can switch to innermost.

R

↳RRRPolo

→TRS2

↳OC

→TRS3

↳Dependency Pair Analysis

Duration:

0:00 minutes